The Expanding of Village Digital Archive Management Competence and Marketing Development for Small and Medium Village Micro Enterprises - Seran, Silverius Tey (Journal of Research in Social Science and Humanities, 2023)
This service aims to increase the competence of village officials in the village digital archives management and the development of marketing techniques for Micro, Small, and Medium Enterprises (MSMEs) in Jatiroke Village. This community service was motivated by the breakthrough and digital innovation of the West Java Government in 2019, which touched various sectors of community service. The achievement of these digital-based programs needs to be supported by qualified Human Resources. Socialization about the digital village program, digital literacy measures, and various forms of digital adaptation need to be continuously promoted, including digital archives management and the variations of marketing techniques for MSMEs products for business actors. With the Participatory Rural Appraisal (PRA) and the FGD (Focus Discussion Group) approach technique, the Village Government can better understand the importance of the effectiveness of archive utilization and MSMEs actors can also understand the importance of marketing adaptation in the midst of globalization.